P019 Audit of prostanoid use in severe Raynaud's and adherence to treatment of digital ulcers in patients with SSc NHSE pathway: commissioning policy cost analysis and alternative therapeutic pathway proposed. (26th April 2021) - Young, Adam; Griffiths, Bridget; Vila, Josephine
Abstract: Background/Aims Severe Raynaud's phenomenon (RP) can lead to digital ulcers (DU), ischaemia, infection and gangrene. In 2015, NHS England published a commissioning policy enabling the use of bosentan for digital ulceration in SSc in patients refractory to intravenous 6-8 weekly prostanoid in combination with sildenafil following standard therapy (including calcium channel blockers (CCB), ACE inhibitors, losartan and fluoxetine). Bosentan is licensed to prevent new DUs in SSc. Specialist MDT ratification and Blueteq registration is required. RCTs showed bosentan reduced the formation of new DU by 30-50% in at risk individuals. It is a well-tolerated drug. It is now off-patent so its cost has reduced from £22, 000 to £650 per year. Aim To audit current departmental practice in patients receiving prostanoid (epoprostenol) for severe RP from any cause and check adherence to the patient pathway for treatment escalation prior to prostanoid therapy. To determine approximate costs of alternative therapeutic approaches. Methods We retrospectively audited patients attending our day unit for epoprostenol infusions over a 12-month period between 2018 and 2019. Using our centre's admissions database and electronic patient records, we identified which oral medications patients were currently co-prescribed or had previously trialled. Using pharmacy data and tariff costings, we calculated the cost of epoprostenol infusions and oral medications with blood monitoring. Results Between 2018 and 2019, 73 patients attended for epoprostenol infusions: 31 SSc, 25 RP, 17 other diagnoses (mixed/undifferentiated CTD, SLE, vasculitis). The mean number of epoprostenol infusions per patient per year was 5.92 days (range 1-25). The percentage of patients who had first been trialled on the following medications include: CCB 77.4%, ACEi/ARB 41.1%, fluoxetine 9.59%, sildenafil 87.1% and tadalafil 25.8%. In the SSc group 22.6% had also trialled bosentan. Only 2 SSc patients (6.45%) had trialled all of the drugs on the pathway prior to prostanoid reflecting the relative lack of efficacy of some first line therapies. The departmental tariff per prostanoid infusion is £450, resulting in an estimated average annual cost of £2700 per patient. The annual cost of supplying bosentan 125mg twice daily plus blood monitoring for the first year is approximately £1350. Conclusion Epoprostenol is used in our unit for patients with severe RP from a range of conditions. Sildenafil and CCB have been trialled in the majority of our patients prior to escalation. Only a minority of patients have received bosentan according to current guidelines and licensing. Given the reduction in cost, combined with the importance of avoiding hospital admissions with COVID-19, we would suggest that bosentan could be used earlier in the treatment pathway for a broader range of indications. NHSE is revising the SSc commissioning policy. Disclosure A. Young: None. B. Griffiths: None. J. Vila: None.